Rubem Alves: education x religion - Silva, Maria de Jesus Reis (2021)
Rubem Alves' concern with education and religion is demonstrated in his works. It is noticed that his literature has a psychoanalytical background added to human life in society, in which he demonstrates his care in situations of pedagogical practice. This research aims to reflect on relevant aspects that, in their works, report the teacher's affectivity in the act of teaching. It consists of bibliographic research designed in a qualitative methodology. The Results show that there are publications that meet Alves' thinking. The enumerated data point to the author's propositions about the confluence between education and religion. His language is coated with subjectivity, which makes us understand all his uneasiness before the world. In relation to school education, he presents subsidies regarding the role of the encouraging and affective teacher in the educational process, especially in the practice of religious teaching. In the final considerations, the pioneering spirit of Alves linked to education and religion is highlighted, as his thinking is a reference to the social facts of contemporary society.